An Overview of Postpartum Psychosis - Siti Annisa Nur Fathia (HM Publisher, 2021)
The Postpartum period is characterized by overwhelming emotional, biological, physical, and social changes. It needs significant personal and interpersonal adaptation, especially in primigravida. Pregnant women and their families are colored by the joyful arrival of a new baby in the postpartum period. But also, the mother in the postpartum period can be vulnerable to a range of postpartum psychosis. Postpartum psychosis is one of serious mental disorder that can result in adverse consequences such as suicide. Suicide is rare during the acute episode, but the rate is high later in the mother’s life and first-degree relatives. Psychosis postpartum is frequently under‑diagnosed, it needs early screening and diagnosis to determine the appropriate treatment as a mandatory part of postpartum care.